Negosiasi’ Sebagai Bagian dari Kompetensi Pragmatik : Kegiatan ABDIMAS di SMA Fons Vitae 1, Jakarta - Putri Rindu Kinasih (Universitas Muhammadiyah Manado, 2024)
Pragmatics can generally be defined as the study of language use in context. This means that someone can be said to have pragmatic skills if they can use language in context appropriately. The students who are currently studying at SMA Fonts Vitae 1 Jakarta are teenagers who are included in the Alpha generation. The Alpha generation's exposure to English and technology makes them quickly rich in information. Therefore, providing English language skills, especially pragmatic skills to the Alpha generation, is very important. This pragmatic skill is important to be taught to students in Indonesia so that they can negotiate with partners from abroad, and welcome foreign tourists without misunderstanding. In the 'Community Service' (ABDIMAS) activity that featured the writer, the presentation and training on negotiation took place at SMA Fonts Vitae 1, Jakarta. The results of the activity showed that the participants were fluent in conversing in English (fluent), but in the negotiation stage participants still experienced obstacles in the crunch time phase. Participants needed time to reach an agreement because the negotiations they conducted focused on the goal of 'defeating' the opponent's argument. Thus, it is important for teachers not only to focus on fluency in speaking but also to train sensitivity to be able to reach a mutual agreement.